STRATEGY OF DAKWAH LDK UMMUL FIKROH IN IMPROVING STUDENT PARTICIPATION AT UIN BANTEN - Umar Atala, Muhammad; Muhammad, Majum; Rahayu, Puji; Alzenna, Della (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to describe the da'wah strategy implemented by the Ummul Fikroh Campus Da'wah Institute (LDK) in an effort to increase student participation at UIN Sultan Maulana Hasanuddin Banten in campus religious activities. The phenomenon of declining student interest in da'wah activities is a challenge that needs to be responded to with an innovative, contextual approach that is in accordance with the characteristics of Generation Z. This study uses a descriptive qualitative method with data collection techniques through in-depth interviews, participatory observation, and documentation studies of core administrators and students involved in LDK activities. Data analysis was carried out using the Miles & Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the LDK Ummul Fikroh da'wah strategy includes a personal approach, utilization of digital media, implementation of thematic activities such as Self Healing, and preparation of programs based on audience research. This strategy is able to increase student participation gradually, although challenges in terms of continuity and adaptation to student dynamics are still obstacles. This study emphasizes the importance of two-way communication, content innovation, and a responsive approach to student needs in making campus da'wah a success